Taxation Of Sukuk In Turkey: As An Alternative Financial Product - Kayhan Refik OKUR; Saim Kayadibi (Journal of Islamic Economics and Philanthropy, 2023)
The markets such as capital markets, financial markets, commodity markets, it creates adomino effect and creates a great impact on the economy. After giving information aboutthe improvement of Islamic finance in Turkey, it describes the kinds of sukuk beingimplemented in Turkey. As a core study, taxation of sukuk in Turkey and sukuk inTurkish tax system are examined specifically. The objective of this paper is to explain thetax advantages and disadvantages on the products offered by the system to those whowant to invest in the alternative finance system or evaluate their savings. In this study,Turkish tax laws were used as the primary source, and the books, theses, articles andconference texts written on this subject were used as the secondary source. This studyincludes the review of the written works, statistics, documents, laws, practices and worksof related international institutions, and open sources of related national institutions.Finally, in this study, recommendations for the necessary regulations for the growth ofthe Islamic finance sector in Turkey and the results obtained from the study are given.Keywords: Islamic Financial Products; Sukuk; Taxation of Sukuk, Sukuk in Turkey.